Management of Prostate Cancer - Klein, Eric A.; Jones, J. Stephen; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2013)
The thoroughly updated and revised third edition of Management of Prostate Cancer provides concise and authoritative guidance to today's best therapeutic regimens for the diagnosis and treatment of prostate cancer.  Highlighting the latest major advances in the field, the book includes chapters on the most controversial areas of prostate cancer – screening, chemoprevention, and active surveillance; updated chapters on genetic risk and progression, biopsy schemes, treatment of complications, and comparative treatment outcomes for surgery; and new chapters on risk factors, new markers, nomograms, and focal therapy. This volume also features overviews of new and emerging drugs and treatment paradigms for castrate resistant disease, advances that promise to extend life and perhaps even cure a subset of men with metastatic disease. With its comprehensive illustrations and contributions from renowned experts in the field, Management of Prostate Cancer, 3rd Edition is an invaluable resource for practitioners in the treatment of prostate cancer.
Epidemiology and Risk Factors -- Twenty years and counting: is PSA still useful in 2010? -- Prostate Cancer Screening: A Review of the Evidence with Clinical Practice Implications -- Beyond PSA: Promising New Markers for Prostate Cancer -- Hereditary Prostate Cancer and Genetic Risk -- Prostate Inflammation and Prostate Cancer -- Molecular Progression of Prostate Cancer: Androgens and Estrogens -- The Role of Obesity and Diet in Prostate Cancer -- Prostate Cancer Risk Reduction by Chemoprevention -- Current Issues in Pathologic Evaluation -- Optimum Prostate Biopsy: Technique and Strategies -- The Utility of Nomograms in Routine Clinical Practice -- Active Surveillance Comes of Age -- Focal Therapy: Prostate Hemiablation as the First Historical Treatment Model for Focal Therapy of Early Stage Prostate Cancer -- Contemporary External Beam Radiotherapy -- Surgery, Brachytherapy, or  External Beam Radiation for Low and Intermediate-Risk Disease? -- The Role for Radical Prostatectomy in Advanced Prostate Cancer -- Radiation Therapy in the Management of Locally Advanced Prostate Cancer -- Clinical Implications of Measuring Quality-of-Life in Early Stage Prostate Cancer -- Treatment Modalities of Post-Prostatectomy Incontinence: A Historical Perspective As Well As Current  Therapy Options -- Management of Biochemical Recurrence After Localized Treatment for Prostate Cancer -- Management of Newly Diagnosed Metastatic Disease -- Pitfalls of Androgen Deprivation Therapy -- Current Management of Castration-resistant Prostate Cancer (CRPC) -- Radiopharmaceuticals and Bone Metastasis.
Keywords: Urology; Oncology .; Surgery; Urology; Oncology; Surgery